PRODUKSI DAN KUALITAS PRODUKSI BUAH TOMAT YANG DIBERI BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR - Sunar Wijaya, Muhd. Nur Sangadji, Muhardi, Agus (AGROTEKBIS, 2015)
This research consisted of two stages, the first stage aimed to determine the best type of liquid organic fertilizer which can be used in fertilizing of tomato plants. The second stages aimed to determine the best concentration of liquid organic fertilizer which can be applied to tomato plants. This research aimed to investigate the responses of tomato plant (Solanum licopersicum Mill.) in terms of its production and quality with the addition of two types of liquid organic fertilizers at different concentrations. This research used a Randomized Completely Block design (RAB) with seven treatments replicated four times. The largest tomato fruit production was found in the organic fertilizer treatment of gremont at concentration of 2.4 ml / 80 ml water, whereas the effect on the quality of the tomato such as average tomato fruit diameter and Vitamin C content was not significant.